Inkorporasi Tepung Garut Dan Buah Pisang Kepok Pada Pembuatan Biskuit Dengan Klaim Tinggi Serat Serta Tinjauan Nilai Cerna Pati In Vitro Dan Gula Total - Nurul Azizah Choiriyah (Poltekkes Kemenkes Mataram, 2020)
Objectives : The purpose of this study was to evaluate biscuit formulations from arrowroot flour and kepok banana for making high dietary biscuits according to BPOM regulation about high dietary fiber claim, also to study about starch digestibility and total sugar content of the biscuits. Methods : Variables of this study was F1 (the ratio of arrowroot flour : kepok banana = 50:125 g), F2 (the ratio of arrowroot flour : kepok banana = 75:100 g) and F3 (the ratio of arrowroot flour : kepok banana = 100:75 g). Results : The results of this study were the F3 biscuits have the highest dietary fiber (15 %). All biscuits fulfill the high dietary fiber claim according to BPOM regulations. Invitro starch digestibilitiy of F1, F2 and F3 biscuits were 35,07 %, 33,15 % and 34,80 %, respectively. Total sugar content of F1, F2 and F3 biscuits were 34,27 %, 32,45 % and 26,85 %, respectively. F3 biscuits have the lowest total sugar content.